Neutrophil phenotypes quantify tissue damage caused by major surgery - de Fraiture, Emma J.; Reniers, Ted; Vreeman, Nathalie E. W.; Rettig, Thijs C. D.; van Santvoort, Hjalmar C.; Bikker, Angela; Vrisekoop, Nienke; Koenderman, Leo; Hietbrink, Falco; Noordzij, Peter G. (Frontiers in Surgery, 2025)
IntroductionMajor surgery triggers an innate immune response that can become excessive, leading to immune suppression and an increased risk of infection. Neutrophils are crucial in this response, and changes in their phenotype are associated with the severity of the innate immune response. This study examines the effect of major surgery on neutrophil phenotypes using fully automated flow cytometry.MethodsIn this prospective single-center cohort study, adult patients undergoing either pancreaticoduodenectomy or on-pump coronary artery bypass grafting (CABG) were enrolled in the (BIGPROMISE) study. Blood samples were collected preoperatively (after anesthesia induction) and postoperatively (immediately after surgery). Neutrophil phenotypes were assessed using automated flow cytometry, with a rapid analysis time of less than 30 min.ResultsThe study included 24 patients undergoing CABG and 12 patients undergoing pancreaticoduodenectomy. Preoperative neutrophil heterogeneity was minimal, but significant postoperative changes in neutrophil subsets were observed in all patients, indicating acute systemic inflammation. Patients who underwent pancreatic surgery showed a more extensive inflammatory response, with 83% in Category 5, compared with 29% in the CABG group.ConclusionsThis is the first study to use fully automated flow cytometry to monitor perioperative changes in neutrophil phenotypes following major surgery. Our findings provide an in-depth readout of the innate immune response and neutrophil activation, highlighting a more pronounced response to pancreatic surgery than to cardiac surgery. Neutrophil phenotyping could serve as a valuable biomarker for patient stratification and management, although larger cohort studies are needed to confirm its predictive value for postoperative complications.